THE REORGANIZATION OF CATHOLIC ACTION OF THE BROTHERS OF THE CHRISTIAN SCHOOLS IN MEXICO: THE BEGINNINGS OF THE YOUNG CATHOLIC STUDENTS (1961-1963) (Tzintzun, Revista de Estudios Históricos, 2024)
This paper reconstructs the beginnings of the Young Catholic Students (YCS) inthe stablishments of the Brothers of the Christian Schools in Mexico between1961-1963. Thus, in the first place, the beginnings of this specialized CatholicAction movement are narrated. Then a description is made of the guidelinesunder which the Lasallian YCS was carried out in Mexico, after which a recountis made of the strategies that were used to disseminate and support this activity.The text ends by exposing the first steps of the North Mexico district with thepurpose of consolidating the Young Catholic Students in its territory.
Keywords: Brothers of the Christian Schools; Specialized catholic action; Young Catholic Students; Catholic student movements